Center-Based Care and Language Development: A Pilot Study on 6-15 Month-Old Persian-Speaking Children - Mohammad Majid Oryadi-Zanjani; Maryam Vahab; Javad Rasouli; Somaye Ghasemi; Atefeh Yazdizade (Shiraz University of Medical Sciences, 2016)
Background: Although it is usually recommended that children begin care after their second or third year, some employed parents have to enroll their children in childcare from under the age of 6 months in Iran. Regardless of when children enter care parents and experts are concern about how childcare affects children's language, social and intellectual development. The aim of this study was to assess the language development in the 6-15 month-old Persian-speaking children enrolled in center-based care. Methods: This was a descriptive, cross-sectional study. The sample size comprised of 13 Persian-speaking 6-15 month-old children who were recruited through consecutive sampling from the Namazi childcare center in Shiraz, Iran. The child's development was assessed by using two assessment tools including the Ages and Stages Questionnaire and the Rossetti Infant-Toddler Language Scale. Descriptive statistics were employed in order to presentation of the findings. Results: Overlay, the results showed that all children could successfully achieve the nonverbal and verbal communication and interaction behaviors. Conclusion: Based on the findings, the quality of childcare centers and the quality of parents-child interaction may be two crucial factors in children's language development. Also, the Rossetti Infant-Toddler Language Scale is a useful assessment tool for Persian-speaking children.